Altitudinal impacts on phytochemical composition and mycorrhizal diversity of Reinwardtia indica Dumort, a medicinally valuable herb - Dhiman, Karishma; Dhalaria, Rajni; Verma, Rachna; Kumar, Dinesh; Hashem, Abeer; Alshaikh, Najla A; Abd-Allah, Elsayed Fathi (BMC plant biology, 2025)
BACKGROUND: Reinwardtia indica, a highly valued ethnomedicinal plant, has been traditionally used to treat various ailments due to its rich phytochemical composition. However, the impact of environmental factors, particularly altitude, on its medicinal properties remains unexplored. This study investigates the effects of altitudinal variation on phytochemicals, mycorrhizal diversity, and soil physico-chemical parameters of R. indica. RESULTS: The phytochemical study of R. indica revealed significant variations in phytochemical content across different altitudes. The methanol extract from the high-altitude site (i.e. Chail, 2000 m) exhibited the highest levels of phenol (142.63 ± 1.88 mg/g GAE), tannins (146.11 ± 1.73 mg/g GAE), flavonoid (51.59 ± 2.20 mg/g RUT), carbohydrate content (485.00 ± 1.52 mg/g GLU), and protein (12.95 ± 0.35 mg/g GAE). GC-MS analysis identified different bioactive compounds with antioxidant, antimicrobial, and antitumor properties. HPLC analysis showed varying rutin content across altitudes, with the highest amount at higher altitude. The plant's association with arbuscular mycorrhizal fungi decreased with increasing altitude, as evidenced by reduced mycorrhizal spore diversity and root colonization. Soil physico-chemical properties like soil pH, organic carbon, phosphorus and nitrogen also increased with the altitude. CONCLUSION: This study demonstrates that altitudinal variation significantly influences the phytochemical composition, mycorrhizal diversity, and soil properties of R. indica. High-altitude sites exhibited increased phytochemical content, particularly phenols, flavonoids, and tannins, suggesting enhanced medicinal value. Conversely, mycorrhizal association decreased with altitude, potentially due to environmental and soil property changes. These findings have implications for optimizing cultivation and conservation strategies for R. indica, highlighting the importance of altitude considerations in harnessing its medicinal potential.
Keywords: léčivé rostliny; Reinwardtia indica; Soil properties; taniny; fytonutrienty; Plants, Medicinal; půda; Mycorrhiza; flavonoidy; Flavonoids; Mycorrhizae; mykorhiza; GC-MS; Altitude; Phytochemicals; nadmořská výška; Tannins; HPLC; Soil